Une approche multirésolution dédiée aux problèmes d’identification - Vidal, Philippe; Allix, Olivier (European Journal of Computational Mechanics, 2002)
This work presents a multisolution strategy intended to decrease the computational cost of a structural identification problem. It is based on the LATIN method [LAD 96] which allows us to represent the solution of a non-linear time-dependent problem as the sum of products of space functions by time functions. The reutilization of the space functions when the parameters change allows us to greatly decrease the cost of all the analyses which are necessary to minimize the distance between experiments and calculations.